Structural insights into aminoacyl-tRNA delivery by EF-Tu and translocation by EF-G - Frank, Joachim (Henry Stewart Talks, 2008)
Schematic of elongation cycle, Role of elongation factors EF-G and EF-Tu, Molecular mimicry of elongation factors, Binding positions of factors and tRNA during elongation cycle, Process of tRNA selection, Proofreading, Role of bases A1492 and A1493, GTP hydrolysis on EF-Tu, tRNA as a molecular spring, Translocation, Intersubunit ratchet motion, Induced fit, FRET studies of ratchet motion, Hybrid states of tRNA, Role of GTP hydrolysis in translocation
Archived at 2020/08/13